Quality Index Method (QIM) for gutted ice-stored hybrid tambatinga (Colossoma macropomum × Piaractus brachypomum) and study of shelf life. (April 2016) - Ritter, D.O.; Lanzarin, M.; Novaes, S.F.; Monteiro, M.L.G.; Almeida Filho, E.S.; Mársico, E.T.; Franco, R.M.; Conte-Junior, C.A.; Freitas, M.Q.
Abstract: Hybrid fish production has increased, leading this sector to occupy a prominent place in the regional and national economy. Thus, the present study aimed to develop a Quality Index Method for gutted ice-stored hybrid tambatinga ( Colossoma macropomum × Piaractus brachypomum ) and estimate its shelf life. Twelve assessors were selected to develop and validate the QIM protocol, and microbiological and physicochemical analyses were performed every other day for 28 days of storage. The final protocol was composed of five quality attributes divided into 10 parameters, with 18 demerit points. Based on the microbiological and physicochemical results, the shelf life of gutted ice-stored hybrid tambatinga is 10 days. Highlights: This study was carried out with the gutted Tambatinga freshwater species. Quality Index Method (MIQ) was developed to assess freshness of the Tambatinga. Shelf live was estimated in 10 days.